The signed Chi-score measure for the classification and mapping of polychotomous data - Visvalingam, Maheswari (The cartographic journal, 1981)
Several polychotomous characteristics, when expressed in chi-score form, exhibit distributions in property space which deviate from the inherent assumptions of the more commonly used methods of cluster analysis. This paper suggests a novel approach to classification which exploits the observed and inferred characteristics of categorised data. The concepts and methods are applied to data on household composition to extract a demographic typology from the one-kilometre grid square population census data for 1971.
Keywords: Cartography – Data processing